Leggi civili e leggi politiche nell’evoluzione giuridica della monarchia francese secondo Montesquieu - Massimiliano Bravi (Montesquieu.it, 2013)
This article aims to reorganized in a coherent order the many observations that Montesquieu devoted to the analysis of French Middle Ages. The Baron of La Brède details the political upheavals that afflicted the early centuries of the French monarchy, but especially he follows the juridical evolution of the fiefs that gradually became private properties disconnected from the hierarchies of vassalage. Montesquieu describes the rise of Hugh Capet as the result of a long process that involved the feudal system in its entirely. The Capetian dynasty completed the development of the French monarchy and adapt it to typological forms that Montesquieu had outlined in the first books of his masterpiece